Hypertriglyceridemia promotes dysfunctions in high-density lipoprotein increasing the cardiovascular risk - Richard Rarison Cavalcante Meneses; Nágila Raquel Teixeira Damasceno; Flávia De Conti Cartolano; Sara Maria Moreira Lima Verde; Letícia Gomes Lira; Mariana Brito Dantas; Glautemberg de Almeida Viana; Mateus Edson da Silva; Ederson Laurindo Holanda de Sousa; Gdayllon Cavalcante Meneses; Jamile Magalhães Ferreira; Tiago Lima Sampaio; et al. (Universidade de São Paulo, 2023)
Abstract Hypertriglyceridemia is associated with several metabolic diseases. The triglycerides (TG) disrupt the cholesterol reverse transport and contribute to increased levels of low-density lipoprotein (LDL). High-density lipoprotein (HDL) acts in cholesterol reverse transport as an anti-inflammatory and antioxidant. This study aims to investigate the role of hypertriglyceridemia in the functionality of HDL. Individuals were divided into 4 groups based on high or low HDL-c and triglycerides levels. Biochemical and anthropometric analysis were performed. This study demonstrated that triglycerides promote dysfunctions on HDL, increasing the cardiovascular risk. Blood pressure was higher in subjects with low HDL. Women presented higher levels of HDL-c and low percentage of fat mass. The highest levels of triglycerides were observed in older age. In addition, high levels of triglycerides were associated with higher total cholesterol and LDL-c levels, non-HDL-c, non-esterified fatty acids, and blood glucose, increasing in the ratio of non-HDL-c/HDL-c and ApoB/ApoA-I. The increase of triglycerides levels progressively impairs the antioxidant capacity of HDL, probably due to a higher occurrence of fatty acid peroxidation in individuals with hypertriglyceridemia. Patients with high HDL and low TG levels increased the Lag Time. Furthermore, a positive correlation was found between TG versus HDL particle size, variables that depend on age and anthropometric parameters.